(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Its extremely low bioavailability is the main problem with poorly soluble medicines. The presence of medications such as carbamazepine, simvastatin, and itraconazole – which are insoluble in both watery and non-aqueous solutions and belong to the BCS class II of the pharmacological classification system – complicates matters even more. Formulation as nanosuspension is a desirable and feasible answer to these problems. The drug is distributed as a so-called nanosuspension, which is a pure, poorly water-soluble drug without any matrix components. The simple synthesis of nanosuspensions can be advantageous for all drugs that are soluble in water. A nanosuspension changes a drug’s pharmacokinetics, boosting safety and efficacy in addition to improving the drug’s soluble condition and low bioavailability. The preparation techniques, article description, and review findings.